1988
DOI: 10.1055/s-0038-1646980
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Postoperative Venous Thrombosis: A Randomized Trial Comparing Unfractionated Heparin with Low Molecular Weight Heparin in Patients Undergoing Total Hip Replacement

Abstract: SummaryA double blind randomized trial comparing subcutaneous enoxaparin (40 mg once daily) with standard unfractionated calcium heparin administered at a dose of 5,000 units every 8 hours in patients undergoing elective hip replacement has been performed. Treatment regimens began 12 hours preoperatively with enoxaparin, 2 hours preoperatively with standard unfractionated calcium heparin, and were continued for 15 days or until discharge. Venography was performed in all patients. Two hundred thirty-seven patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
92
1
3

Year Published

1998
1998
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(99 citation statements)
references
References 21 publications
3
92
1
3
Order By: Relevance
“…The overall bleeding rate of 2% after major orthopaedic surgery is comparable with the clinical outcome of large randomized trials (10). The rate of symptomatic DVT and PE during the hospitalization was even lower than expected, confirming the high efficacy of thromboprophylaxis with LMWH in daily clinical practice.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The overall bleeding rate of 2% after major orthopaedic surgery is comparable with the clinical outcome of large randomized trials (10). The rate of symptomatic DVT and PE during the hospitalization was even lower than expected, confirming the high efficacy of thromboprophylaxis with LMWH in daily clinical practice.…”
Section: Discussionsupporting
confidence: 57%
“…Randomized controlled trials confirmed that thromboprophylaxis with low-molecular-weight heparins (LMWH) substantially reduces the rate of DVT and PE (7)(8)(9). The rate of bleeding complications after major orthopedic surgery with thromboprophylaxis approximates 2% (10). However, because of the different pharmacodynamic properties, LMWH are not interchangeable for the various indications.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers use a decrease in hemoglobin greater than 2 g/dL in the definition of major bleeding [11], and the rate of major bleeding frequently is reported as a safety outcome in trials of thromboprophylaxis [9,13,16,23]. We found such a decrease in hemoglobin for the majority of patients until the first postoperative injection (83% versus 90%) and the day after surgery (93% versus 90%), which indicates a decrease in hemoglobin is a poor parameter for defining major bleeding in patients undergoing THA.…”
Section: Discussionmentioning
confidence: 99%
“…Type of antithrombotic drug, dosage, and timing of the first dose may influence bleeding and development of thrombosis. Low-molecular-weight heparins (LMWHs) are widely used antithrombotics because of their favorable efficacy-to-safety profiles [9,23], but the best timing of the first dose remains controversial [24,28]. Preoperative initiation 12 hours before surgery has been based on the premise that DVT starts during surgery and that preoperative initiation is necessary to optimize antithrombotic effectiveness [17,27].…”
Section: Introductionmentioning
confidence: 99%
“…Since there is no clear recommendation regarding the dose of LMWHs in pregnancy, we used 40 mg of enoxaparin, as this is the recommended dose either for prophylaxis in patients at high risk of VTE (major orthopedic surgery [19] or cancer surgery [20], acutely ill medical patients [21]), or, according to some authors [4], for obstetric thromboprophylaxis. The timing of fetal blood sampling (3 h after the enoxaparin injection) corresponds to the time of peak blood levels of enoxaparin in the mother [8] and also to the peak of placental blood flow, allowing most drugs capable of crossing the placenta to do so in a very short period of time [16].…”
Section: Discussionmentioning
confidence: 99%